2016
DOI: 10.1016/j.ejor.2015.07.062
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of the UK and Italian small businesses using Generalised Extreme Value models

Abstract: This paper presents a cross-country comparison of significant predictors of small business failure between Italy and the UK. Financial measures of profitability, leverage, coverage, liquidity, scale and non-financial information are explored, some commonalities and differences are highlighted. Several models are considered, starting with the logistic regression which is a standard approach in credit risk modelling. Some important improvements are investigated. Generalised Extreme Value (GEV) regression is appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 52 publications
(90 reference statements)
6
49
0
Order By: Relevance
“…The BGEVA model has been then improved by Calabrese, Marra, and Osmetti (2016) . Several studies ( Andreeva et al, 2016;Calabrese et al, 2016;Calabrese & Osmetti, 2013;2015 ) have shown that the GEV model outperforms the logistic and the probit models even if the percentage of ones in the sample is one per cent.…”
Section: Gev Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The BGEVA model has been then improved by Calabrese, Marra, and Osmetti (2016) . Several studies ( Andreeva et al, 2016;Calabrese et al, 2016;Calabrese & Osmetti, 2013;2015 ) have shown that the GEV model outperforms the logistic and the probit models even if the percentage of ones in the sample is one per cent.…”
Section: Gev Modelmentioning
confidence: 99%
“…If we classify the rare events as ones, the major drawback of these approaches is that they underestimate the probability of binary rare events for values close to one, such as bank defaults or bail-outs ( Calabrese & Osmetti, 2015;King & Zeng, 2001;Wang & Dey, 2010 ). To overcome this limitation, a model has been proposed in the operational research literature ( Andreeva, Calabrese, & Osmetti, 2016;Calabrese & Osmetti, 2013;2015;Marra, Calabrese, & Osmetti, 2014 ) -the Binary Generalised Extreme Value Additive model, BGEVA (GEV model in the parametric form). This approach is particularly suitable for binary rare events data, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Tsaih et al [2] used fundamental characteristics, bank borrow relationship, personal trade history, and industry factors includ ing business cycles, macroeconomic factors as input features and developed a probit model to evaluate enterprise credit. Similarly, Andreeva, Calabrese, and Osmetti [3] ext racted profitability, leverage, coverage, liquid ity, scale and non-financial information and applied generalized extreme value models to UK and Italian small businesses. Serrano-Cinca, Gut ierrezNieto and Reyes [4] considered financial informat ion and social impact informat ion to cred it modeling, while Fernandes and Artes [5] introduced spatial dependence into credit risk assessment to imp rove the performance of credit scoring.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As can be seen from literatures, enterprise fundamental characteristics, financial reports, social and environment indicators are involved in enterprise credit risk evaluation [1][2][3][4][5][6][7], and the basic rules, and several sophisticated models are designed and implemented in cred it scoring [8][9][10][11][12][13][14]. Both the novel indicators and the state-of-art models can imp rove the performance of credit risk evaluation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to perform a factor analysis of the key indicators of a segment, generalized reporting information will not suffice therefore analysts fall upon a specific list of additional data contained in the system of management accounting that constitutes a trade secret (Andreeva G., 2016, Hafid I., 2016.…”
Section: Introductionmentioning
confidence: 99%